Reduced body length and morphological disorders in Chrysomya albiceps (Diptera: Calliphoridae) larvae reared on aluminum phosphide-treated rabbits - Saeed El-Ashram; Noura A. Toto; Abeer El Wakil; Maria Augustyniak; Lamia M. El-Samad (Scientific Reports, 2022)
Abstract Assessing the time of death based on the growth and development of insects is a critical task in forensic entomology. The rate of larvae development can be affected by a variety of toxins, including pesticides. Aluminum phosphide (AlP) is a low-cost insecticide that has yet to be tested for entomotoxicological significance, despite the fact that it is frequently the cause of fatal poisoning. In this study, we measured the body length of Chrysomya albiceps larvae reared on the carcasses of rabbits poisoned with AlP and analyzed the morphological changes of the larvae reared on the carcasses of rabbits poisoned with AlP. The concentration of AlP in the body of the larvae was significantly lower than in rabbit tissues. Insects from the AlP group had a significantly lower gain in body length. Furthermore, deformities in the larvae were found. Smaller respiratory spiracles were found, as well as a deformed small posterior end with hypogenesis of the posterior respiratory spiracles. Thus, disturbed growth and development of carrion flies found at a crime scene could indicate pesticide poisoning, such as aluminum phosphide.